2011
DOI: 10.1111/j.1365-2133.2011.10427.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐of‐illness of patients with chronic hand eczema in routine care: results from a multicentre study in Germany

Abstract: Patients with CHE refractory to topical steroids incur marked costs to society. The costs increase disproportionately with escalating treatment stages, especially in patients admitted to hospital. Hence, new treatments may help to reduce the societal costs of CHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 22 publications
3
72
3
8
Order By: Relevance
“…CHE exacts a considerable clinical burden and is associated with high rates of sick leave, loss of earnings and, for some patients, requires a change of job or exclusion from the workforce (4)(5)(6)(7)(8)(9)16). This is the first study to investigate the relationship between costs of illness and whether CHE is occupational or unrelated to work, based on 2 different surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHE exacts a considerable clinical burden and is associated with high rates of sick leave, loss of earnings and, for some patients, requires a change of job or exclusion from the workforce (4)(5)(6)(7)(8)(9)16). This is the first study to investigate the relationship between costs of illness and whether CHE is occupational or unrelated to work, based on 2 different surveys.…”
Section: Discussionmentioning
confidence: 99%
“…The recent multicentre German study to determine the cost-of-illness in patients with CHE in routine care (6) showed that CHE costs are correlated with disease severity. The analysis presented here adds a further important cost driver -CHE caused-by and impactingon work function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CHE is the most common occupational disease and therefore of high socioeconomic impact (11,12). Health-related costs and quality of life in CHE have also been investigated in several studies during the past years (13)(14)(15)(16). It has become clear that prevention of this costly and disabling disease is an issue of great importance.…”
mentioning
confidence: 98%
“…Severe hand eczema resulting in prolonged disability is associated with a high health economic burden and significant loss of quality of life (7,8). Although numerous treatment options are available, the management of CHE is often difficult and unsatisfactory.…”
mentioning
confidence: 99%